2016
DOI: 10.1111/jai.13045
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different cycles of starvation and re-feeding on growth and body composition in rainbow trout (Oncorhynchus mykiss, Walbaum, 1792)

Abstract: This study was designed to investigate the effects of starvation and re-feeding cycles on the growth performance and body chemical composition of Oncorhynchus mykiss juveniles. A total of 360 juveniles with initial mean weights (IW) of 8.46 AE 0.07 g (n = 360) were stocked into 400-L tanks in triplicate for each group, with 30 juveniles per tanks. The control group received regular feed, as is the common practice. The three other groups were periodically starved: 1 day starvation followed by 6 days re-feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…However, in a prolonged experiment, accelerated growth might dominate, as indicated by the CC analysis for the 2DPW and the 4DPW groups, but not for 1DPW. This value is considered proof of compensation growth, as observed in pikeperch, Sander lucioperca (Mattila et al, 2009) and rainbow trout, Oncorhynchus mykiss (Taşbozan et al, 2016). Bavčević et al (2010) reported compensation in body weight of gilthead sea bream (Sparus aurata), but not length, under restriction and refeeding cycles.…”
Section: Discussionmentioning
confidence: 69%
“…However, in a prolonged experiment, accelerated growth might dominate, as indicated by the CC analysis for the 2DPW and the 4DPW groups, but not for 1DPW. This value is considered proof of compensation growth, as observed in pikeperch, Sander lucioperca (Mattila et al, 2009) and rainbow trout, Oncorhynchus mykiss (Taşbozan et al, 2016). Bavčević et al (2010) reported compensation in body weight of gilthead sea bream (Sparus aurata), but not length, under restriction and refeeding cycles.…”
Section: Discussionmentioning
confidence: 69%
“…The analysis of such region provides information on vibrational modes associated with the molecular composition of different functional groups belonging to lipids, proteins, and carbohydrates [50]. In this study, the contribution provided by carbohydrates was not taken into consideration due to the negligible carbohydrate content in the trout muscle tissue [51]. The peak assignment is reported in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 If biometrics cannot be conducted consistently, the determination of compensation coefficients could facilitate the determination of CG. [55][56][57] Compensation coefficient greater than 1 indicates compensatory growth, and it is calculated as follows:…”
Section: Mechanisms and Degree Of Compensationmentioning
confidence: 99%
“…CC=ΔT*ΔC −1 , where ΔT as the weight gain in deprived animals (g) divided by the number of feeding days and ΔC is the weight (g) in control animals divided by the number of feeding days. 57,58 The process of compensatory growth is still not completely understood, 24,59 but some mechanisms such as hyperphagia and improved feed conversion have been clearly identified as drivers…”
Section: Mechanisms and Degree Of Compensationmentioning
confidence: 99%
See 1 more Smart Citation